2019
DOI: 10.4236/aces.2019.91008
|View full text |Cite
|
Sign up to set email alerts
|

Protein Enrichment of Potato Peels Using Saccharomyces cerevisiae via Solid-State Fermentation Process

Abstract: In order to add value to potato peels and also curb their environmental pollution problems, this study investigated the protein enrichment of potato peels with Saccharomyces cerevisiae via Solid-State Fermentation (SSF). SSF is a fermentation process which involves solid matrix and is carried out in absence or near absence of free water. SSF of potato peel mashed was carried out with S. cerevisiae at 30˚C, pH of 5.5, moisture adjustment between 40 and 90%, addition of ammonium sulphate and urea salts as nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This report measured the protein content of 15.45% of potato peels. A research report by Maxwell et al 45 has measured the protein content of 12.5% while reporting the effect of Saccharomyces cerevisiae on protein enrichment of potato peels using solid-state fermentation process. Onuguh et al 46 have recorded almost similar level of fat from potato peels that is 0.28%.…”
Section: Resultsmentioning
confidence: 99%
“…This report measured the protein content of 15.45% of potato peels. A research report by Maxwell et al 45 has measured the protein content of 12.5% while reporting the effect of Saccharomyces cerevisiae on protein enrichment of potato peels using solid-state fermentation process. Onuguh et al 46 have recorded almost similar level of fat from potato peels that is 0.28%.…”
Section: Resultsmentioning
confidence: 99%
“…In the rumen, these probiotics scavenge oxygen, stabilize rumen pH, and produce several beneficial nutrient cofactors such as organic acids, peptides, and vitamins that stimulate and facilitate the growth and proliferation of the beneficial rumen microbiota (Elghandour et al 2022), resulting in improved of nutriment digestibility, feed palatability, growth performance and milk production, animal health, and providing a clear economic advantage for sheep, buffalo, calf, and cow breeding (Anjum et al 2018;Villot et al 2019;Wang et al 2022;Xue et al 2022;Hiltz et al 2023). In recent years, many experiments have proved that fermenting feeds such as potato peel, orange pulp, sobyan meals, and food waste with Saccharomyces cerevisiae before offering them to animals is a good strategy to reduce their antinutritional factors and improve their nutritional value (Hassaan et al 2015;Maxwell et al 2018;Guerra et al 2021;Li et al 2022). The LY, including the Saccharomyces cerevisiae, is the best microorganism that effaces fermented feeds in an aerobic environment and enhances their quality (Rai et al 2019;Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi, "Generally Regarded As Safe" (GRAS), because they do not usually produce metabolites of human health hazard, are important for application in solid-state fermentation, as a result of their traditional role in fermentation, and improvement of nutritional value of foods (Nasseri et al, 2011;Aruna et al, 2017). Studies have shown the potential for peels of some agro-industrial produce as suitable substrates for valueaddition through solid-state fermentation using non-toxic fungi which fall into the category of GRAS (Iyayi & Losel, 2001;Akintomide & Antai, 2012;Dawish et al, 2012;Ezekiel & Aworh, 2013;Azam et al, 2014;Aruna et al, 2018;Maxwell et al, 2019). Few studies have focused on yam peels in the West African sub-region (Aruna et al, 2017;Aruna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%